The Direction of Arrival Location Deception Model Counter Duel Baseline Phase Interferometer Based on Frequency Diverse Array - Ge, Jiaang; Xie, Junwei; Chen, Chushu; Wang, Bo (Frontiers in Physics, 2021)
With the emergence and development of the passive localization, the radiation source is more visible for the location system which endangers their survival, therefore, there is an urgent demand for the radio frequency (RF) stealth technology. An effective method to realize RF stealth is location deception, therefore, for the passive localization system, this paper proposes a DOA location deception method using the frequency diverse array (FDA) against the duel baseline phase interferometer. Since the direction-finding of the dual baseline phase interferometer is based on the received signal with fixed frequency, the FDA signal have the deception effect on the interferometer owing to the introducing of the small frequency increment. Considering the influence of the frequency increment sequence on the deception effect, we derive the optimizations of DOA location deception via the average location deviation for the sampling time in the case of no noise and noise, respectively. Besides, considering the time dependency of the beam, we investigate the average SNR (ASNR) and the corresponding CRLB to verify the proposed method. Numerical examples and simulations show that the proposed method can counter the interferometer by realizing location deception.